New Visions and Re-Visions in 20th and 21st Century French Literature - Eileen Angelini (Studies in 20th & 21st Century Literature, 2012)
In the twentieth century, the “death of the author” was proclaimed by literary critics. Since then, there has been a shift in focus from text to reader. This reorientation called forth changing critical paradigms, taking us from modernism to postmodernism and beyond...
Keywords: modernism; postmodernism; “death of the author”; focus on reader; shift of focus; twentieth century; twenty-first century; 20th century; 21st century